Progress in the study of the role of mesenchymal stem cell exosomes in heart transplant rejection - LIU Dezhao; ZENG Zhiyu (Guangxi Yike Daxue xuebao)
Heart transplantation is an effective treatment for patients with end-stage heart failure, but faces challenges such as organ shortage and rejection. Mesenchymal stem cells (MSCs) hold promise as a potential therapy for attenuating heart transplant rejection due to their immunomodulatory activity. However, their clinical application is limited by issues such as the low MSC survival rate and insufficient homing efficiency after the transplantation. Exosomes (Exos) are important carriers for intercellular information delivery, with the advantages of low immunogenicity and high stability. MSC-exos can effectively deliver immunomodulatory molecules, promote tissue repair and immune tolerance, and thus attenuate heart transplant rejection. Studies have shown that MSC-exos can effectively overcome the deficiencies of MSCs cell therapy and are expected to be a new way to better attenuate heart transplant rejection. Therefore, this article reviews the current research status of heart transplantation and the research progress of MSC-exos in the field of heart transplantation in recent years, with the aim of providing new ideas to better improve the survival rate of heart transplant patients.